(untitled) (Tạp chí Y học Cộng đồng, 2022)
Background: Hand hygiene (VST) is the simplest, most effective and most important measure that contributes to reducing hospital-acquired infections, ensuring the safety of health workers and improving the quality of patient care. Objectives: Describe the knowledge and practice of hand hygiene of medical staff at the National Eye Hospital and analyze some related factors. Methods: Cross-sectional survey, quantitative research. Results: This study collected information from 323 health workers (NVYT), National Eye Hospital through questionnaires and observation using checklists. The research results show that the knowledge and practice of hand hygiene in the control of hospital-acquired infections of health workers is quite good. Conclusion: The rate of health workers with knowledge of hand hygiene reached 74.9%. The rate of health workers with practices of hand hygiene reached over 85%. There are 4 factors related to knowledge of hand hygiene including: age, working position, working time and professional qualifications. Three factors related to practices of hand hygiene including: Gender, working position and time of training on infection control (p<0.05).